Pengukuran Layanan Pada Aplikasi Mobile JKN Menggunakan Metode Servqual - Andi Saryoko; Hendri Hendri; Sulaeman Hadi Sukmana (LPPM Universitas Bina Sarana Informatika, 2019)
The Indonesian people in registering as members of the BPJS for Health can now be done in several ways: 1) registration by coming directly to the nearest BPJS office, 2) being able to register online on a computer, internet connected laptop on the https: / page /daftar.bpjs-kesehatan.go.id/ or 3) register online on the JKN mobile application with a smartphone or mobile. Research to analyze the level of community satisfaction with BPJS Health online registration on the JKN mobile application by applying the servqual method. In registering BPJS Health members online, the application provider must be able to give full attention to service quality (SERVQUAL). In the context of measuring service quality variables, Parasuraman, Zeithaml and Berry (1998) identified five dimensions of service quality measures including: Reliability, responsiveness, Assurance, Direct evidence (Tangibles), and Empathy (Empathy). This study aims to examine the level of satisfaction of BPJS Health members towards online registration services at BPJS Health especially for the Jakarta area by applying the SERVQUAL method, and to find out what factors should be prioritized on online registration with the JKN mobile application in order to meet community expectations. From this scientific research, it is hoped that it can be published in one of the national journals and can be announced at the National scientific meeting.